PENGARUH AUDIT REPORT LAG, KOMITE AUDIT DAN FINANCIAL DISTRESS TERHADAP OPINI AUDIT GOING CONCERN - Khasanah, Uswatun; Napisah, Napisah (JURNAL AKUNTANSI BARELANG, 2024)
This research was conducted with the aim of determining the influence of Audit Report Lag, Audit Committee, and Financial Distress on Going Concern Audit Opinions in transportation and logistics sub-sector service companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. This type of research is quantitative research using secondary data which can be accessed from old or personal websites of transportation sub-sector service companies listed on the Indonesia Stock Exchange (BEI). This research uses a purposive sampling method, namely by taking samples from the population based on certain criteria. The research sample is based on the criteria of 19 companies with a research period of 5 years. The data analysis method used in this research is a statistical method that uses a logistic regression equation. Data analysis began by processing the data with Microsoft Excel, then logistic regression testing was carried out using Eviews version 12 software. The results of this research show that Audit Report Lag has an effect on going concern audit opinion; The audit committee has no influence on going concern audit opinion; Financial Distress influences going concern audit opinion.